2019
DOI: 10.1007/s10120-019-00968-2
|View full text |Cite
|
Sign up to set email alerts
|

Conversion gastrectomy for stage IV unresectable gastric cancer: a GIRCG retrospective cohort study

Abstract: Background The aim of this study is to report the experience with conversion surgery from six Gruppo Italiano Ricerca Cancro Gastrico (GIRCG) centers, focusing our analysis on factors affecting survival and the risk of recurrence. Methods A retrospective, multicenter cohort study was performed in patients who had undergone conversion gastrectomy between 2005 and 2017. Data were extracted from a GIRCG database including all metastatic gastric cancer patients submitted to surgery. Only stage IV unresectable tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
57
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(66 citation statements)
references
References 22 publications
6
57
0
Order By: Relevance
“…Furthermore, the same study identi ed R0 resection as an independent predictor for a favorable OS after multivariate analysis [20]. An Italian retrospective cohort study also identi ed residual tumor status after conversion surgery (R0 vs. R1) as an independent prognostic factor for progression-free survival among patients with stage IV unresectable gastric cancer following multivariate analysis [22]. The present study obtained an R0 resection rate of 94.7% (18/19).…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Furthermore, the same study identi ed R0 resection as an independent predictor for a favorable OS after multivariate analysis [20]. An Italian retrospective cohort study also identi ed residual tumor status after conversion surgery (R0 vs. R1) as an independent prognostic factor for progression-free survival among patients with stage IV unresectable gastric cancer following multivariate analysis [22]. The present study obtained an R0 resection rate of 94.7% (18/19).…”
Section: Discussionsupporting
confidence: 63%
“…Considering that conversion surgery after chemotherapy allows for the removal of viable tumor cells in primary sites and lymph nodes, its clinical advantage may lie in its ability to eliminate chemoresistant tumor cells.Clinical indications for conversion surgery after chemotherapy among in patients with P1 gastric cancer have remained uncertain. However, recent studies have demonstrated the clinical importance of R0 resection in conversion surgery[20][21][22]. Fukuchi et al reported that patients with unresectable gastric cancer undergoing R0 and R1/R2 resections had a 5-year OS rates of 49% and 15%, respectively…”
mentioning
confidence: 99%
“…Some of previous studies suggested that SRCC is less chemo‐sensitive than non‐SRCC cancers, so the value of palliative gastrectomy plus chemotherapy may be even higher in stage IV gastric SRCC than NOS. In addition, several recently published studies proved that improved long‐term survival was observed among stage IV GC patients who underwent conversion surgery (primary tumor resection performed in initially unresectable metastatic cancer after responding to chemotherapy) . This also cast light on the therapeutic role of palliative surgery strategies in stage IV gastric SRCC patients.…”
Section: Discussionmentioning
confidence: 94%
“…Currently, chemotherapy is considered as an initial treatment in patients with stage IV gastric cancer including liver metastasis [8]. Furthermore, conversion surgery has been focused on as a promising therapeutic strategy in responders after chemotherapy [18]. To date, we have targeted chemotherapy responders with technically resectable metastasis and without peritoneal metastasis for conversion surgery in patients with stage IV gastric cancer.…”
Section: Discussionmentioning
confidence: 99%